Diagnostic accuracy of double density sign on CT scan of para-nasal sinuses for fungal sinusitis taking microbiology culture as gold standard - Hadia Wali; Shayan Shahid Ansari; Mohammad Umair; Abdullah Faisal Dar (Journal of the Pakistan Medical Association, 2024)
Objective: To compare double-density sign on non-contrast computed tomography scan of paranasal sinuses with fungal sinusitis on histopathology. Method: The prospective, cross-sectional, randomised study was conducted at the Shifa International Hospital, Islamabad, Pakistan, from July 1, 2021, to June 30, 2023, and comprised patients of either gender aged 20-60 years who were set to undergo functional endoscopic sinus surgery. Demographic characteristics and non-contrast computed tomography scan findings were recorded pre-operatively, while microbiological and histopathology results were recorded post-operatively. The microbiological finding was taken as the gold standard. Data was analysed using SPSS 23. Results: Of the 201 patients, 123(61.2%) were males and 78(38.8%) were females. The overall mean age was 41.62±8.52 years. The diagnostic accuracy of a double-density sign on computed tomography scan showed sensitivity 90%, specificity 90.8%, positive predictive value 84%, and negative predictive value 94.4%. Conclusion: A higher rate of sensitivity and specificity indicated that non-contrast computed tomography scan was an effective modality that could be used for the diagnosis of fungal sinusitis. Key Words: Diagnostic accuracy, Fungal sinusitis, Double density.